Nanoporous Copper Pattern Fabricated by Electron Beam Irradiation on Cu3N Film for SERS Application. Issue 2 (1st October 2018) - Du, Yun; Yin, Yin; Wang, Jiawei; Wang, Zongli; Li, Charong; Baunack, Stefan; Ma, Libo; Schmidt, Oliver G.
Abstract : Copper nanostructures have aroused extensive research interests due to their wide applications in electronics, catalysis, and photonics. Here, a novel strategy to fabricate copper nanoporous structures by illuminating electron beam on as‐prepared copper nitride thin films is reported. This electron beam‐based direct writing method provides a precise control of the nanoporous sites on substrates. Experimental results reveal significant surface‐enhanced Raman scattering (SERS) for copper porous nanostructures compared with flat copper nitride thin films due to localized surface plasmon resonances supported at the nanopores. This work provides a maskless method to prepare copper nanoporous structures from copper nitride films and implies an efficient SERS platform for sensitive molecular diagnostics. Abstract : A new strategy of fabricating copper nanoporous structures is investigated by illuminating electron beam on deposited copper nitride thin films. Nanoporous copper can be well controlled at desired sites by local decomposition using this maskless method. Proof‐of‐concept measurements reveal the ability for surface‐enhanced Raman scattering due to the localized surface plasmon resonances supported at the nanopores.